THE STRUCTURE AND FUNCTION OF SPATIAL PERSPECTIVE AND SPATIAL POINT OF VIEW - Turumova Nilufar Erkinovna (International Scientific and Current Research Conferences, 2023)
Spatial perspective and spatial point of view are critical elements in narrative and visual arts, shaping how audiences perceive and interpret events, characters, and environments. This article examines the structure and function of these spatial dimensions, highlighting their role in creating depth, directing focus, and influencing emotional and intellectual engagement. By analyzing examples from literature, film, and visual arts, this study explores how spatial perspectives and viewpoints are constructed and how they function as tools for storytelling and meaning-making.